Operations management : processes and value chains - Krajewski, Lee J.; Ritzman, Larry P. (New Delhi : Prentice-Hall, 2005)
Business
Keywords: Operations management; Operations strategy; Process design; Process analysis; TQM; SPC; Managerial practice; Value chains